Organic enrichment at salmon farms in the Bay of Fundy, Canada: DEPOMOD predictions versus observed sediment sulfide concentrations - BD Chang (Inter-Research, 2014)
A model for predicting benthic impacts of fish farms (DEPOMOD) was used to predict organic carbon deposition rates at 6 salmon farms in the southwestern New Brunswick (SWNB) area of the Bay of Fundy, Canada. Model predictions of the seafloor area with elevated deposition rates were compared to the areas of seafloor with elevated observed sulfide concentrations. DEPOMOD predictions with resuspension appeared to overestimate the rate of resuspension of waste particles where current speeds were moderate to high; therefore, model runs without resuspension were used for comparisons. There were no consistent relationships between current speeds and the predicted (without resuspension) area with elevated deposition rates and the areas with elevated sulfide concentrations. There was a positive relationship between the areas with elevated deposition rates and the areas with elevated sulfide concentrations at 3 sites, with a better fit when the DEPOMOD runs used average daily feeding rates during 1 mo periods including the date of sediment sampling (compared to average feeding rates during 3 mo feeding periods ending near the date of sampling). Because the predicted area with elevated deposition rates (without resuspension) was strongly correlated with the feeding rate, it is important that the appropriate feeding rate be used in model runs. At sediment sampling stations where predicted deposition rates were low, sulfide concentrations were usually low; however, at sampling stations where predicted deposition rates were elevated, sulfide concentrations showed high variability. Implications for the use of DEPOMOD for management of the salmon aquaculture industry in SWNB are discussed.